Associations between polymorphisms in coagulation-related genes and venous thromboembolism: A meta-analysis with trial sequential analysis. Issue 13 (March 2017) - Jiang, Jun; Liu, Kang; Zou, Junjie; Ma, Hao; Yang, Hongyu; Zhang, Xiwei; Jiao, Yuanyong
Abstract: Background: Recently, several studies showed that the polymorphisms in the coagulation-related genes might be associated with venous thromboembolism (VTE); however, the results were still controversial. We performed a meta-analysis with trial sequential analysis to investigate the associations between the endothelial cell-activated protein C receptor (EPCR) rs9574, F11 rs2289252, F11 rs2036914, FGG rs2066865, FGG rs1049636, CYP4V2 rs13146272, SERPINC1 rs2227589, and GP6 rs1613662 polymorphisms with the risk of VTE. Methods: We searched both the common English-language databases and the Chinese literature databases. Two authors selected studies according to inclusion and exclusion criteria. Crude odds ratios with 95% confidence intervals (CI) were calculated to estimate the strength of this association. Between-study heterogeneity was assessed with the chi-square-based Q test and the I 2 statistic. Results: Overall, a total of 20 studies were included. The meta-analysis revealed that the F11 rs2289252, F11 rs2036914, FGG rs2066865, and CYP4V2 rs13146272 polymorphisms were closely related to the development of VTE in the white race under the best genetic models after multiple testing adjustments. The EPCR rs9574, FGG rs1049636, SERPINC1 rs2227589, and GP6 rs1613662 polymorphisms might be potential candidates in the pathogenesis of VTE, but trial sequential analyses and sensitivity analyses indicated that the evidences were limited. Larger scale studies were demanded to avoid false-positive outcomes. Conclusions: Finally, our study demonstrated the important role of rs2289252, rs2036914, rs2066865, and rs13146272 polymorphisms in the development of VTE in the white race. Rs9574, rs1049636, rs2227589 and rs1613662 polymorphisms might be risk factors of VTE. However, more studies involving diverse races are needed to probe the ethnic difference and the underlying mechanisms of significant associations. Abstract : Supplemental Digital Content is available in the text